The metaverse: A new frontier for dental education - Hashim, Nada; Babiker, Rasha; Padmanabhan, Vivek; Mohamed, Riham; Ahmed, Ayman; Rahman, Muhammed Mustahsen (Edelweiss Applied Science and Technology, 2025)
Integrating the metaverse into dentistry education offers a significant opportunity to transform how dental students learn and interact with their educational environment. The metaverse is a digital space that combines augmented reality (AR), virtual reality (VR), and blockchain technologies to provide an immersive and participatory experience. This review assesses the potential benefits and applications of the metaverse in dental education and discusses the challenges and considerations for its effective implementation. Additionally, it highlights the importance of a comprehensive and coordinated strategy, which involves collaboration among educators, technologists, and regulatory bodies, to establish a solid foundation for the use of the metaverse in dental education.